A novel public-private partnership to increase the penetration of energy storage systems in distribution level. (June 2023) - Kazemi, Mostafa; Tabatabaei, S. Sepehr; Moslemi, Niki
Abstract: This paper presents a new incentive-based approach to increase the penetration of energy storage systems in distribution level. The proposed model is based on a public-private partnership which is appropriate for developing countries with budget deficit. By increasing the buying price from energy storage systems during peak-periods and providing discount on selling prices to the energy storage systems during off-peak periods, private investors are encouraged to install energy storage systems. The public section could use the installed capacity of energy storage systems for different purposes such as peak shaving. In the presented method of this paper the direct connection between the operator and the household energy storages is not required, through applying the incentive prices for energy consumption/production of energy storages. The proposed public-private partnership model of this paper is a bi-level optimization model. By implementing Karush-Kuhn-Tucker (KKT) conditions the equivalent single level optimization model is evaluated. The nonlinear model is linearized using strong duality theory and big M method. The applicability of the proposed method is analyzed using the real data of Yazd's network. In the numerical section it has been shown that a proper partnership between the public and private sectors is crated. The peak load is shaved properly, while the private household makes a reasonable profit through their investment. The penetration of the energy storage systems is increased without direct investment of the public sectors and the expansion cost is significantly reduced trough elimination of communication systems. Highlights: Proposing a new approach for increasing the penetration of energy storage systems Designing a public-private partnership reducing the cost of expanding energy system Elimination of telecommunication systems using incentive prices for energy storages Linearization of the model using SDT and KKT conditions without any approximation